Novel high entropy alloys of FexCo1-xNiMnGa with excellent soft magnetic properties. (September 2018) - Zuo, Tingting; Zhang, Min; Liaw, Peter K.; Zhang, Yong
Abstract: The Fex Co1-x NiMnGa (FeNiMnGa, Fe0.5 Co0.5 NiMnGa, and CoNiMnGa) alloys are designed based on the high entropy effect and the model of the Ni2 MnGa alloy in searching for the potential functional magnetic alloys with improved mechanical properties. Although the substitution of Ni by Fe or Co can reduce the ordering of the phases due to the high mixing of entropy, these three alloys are composed of ordered phases, which lead the alloys to show the brittle deformation behavior with the combined intergranular and cleavage fracture mechanisms. These alloys exhibit excellent soft magnetic properties with very low saturation magnetostriction coefficients. For CoNiMnGa alloy, the saturation magnetization can be 115.92 emu/g, and the Curie temperature is about 657.3 K. The addition of Co enhances the exchange interaction and makes the alloy demonstrate potential applications at higher temperatures. In addition, the single disordered solid-solution phase-formation rule of high entropy alloys is evaluated, which can shed light on the HEAs design. Highlights: Fex Co1-x NiMnGa alloys are designed based on the high entropy effect and in search of potential functional magnetic alloys. The Fex Co1-x NiMnGa alloys compose of ordered phases with combined intergranular and cleavage fracture mechanism. These alloys exhibit excellent soft magnetic properties with very low saturation magnetostriction coefficient. The single disordered phase formation rule of high entropy alloys is verified.